Inoculation Of Novel Consortium For Ameliorating Paddy Cultivation In Saline Soil (International Journal of Food and Nutritional Sciences, 2022)
A novel microbial consortium was investigated for promoting paddy growth in fields on saline soil without chemical fertilizers. Four popular rice varieties Sarjoo-52; NDR-359; Indrasan and Sambha Mahsuri (BPT 5204) studied for two consecutive years. Rice varieties were given novel fungal (T2) and bacterial (T3) consortium treatments. An un-inoculated treatment was also taken as control (T1). Changes in soil physico-chemical, biological properties and plant growth promotion were studied. Statistical analysis performed to assess significant differences in effects under different treatments. Sarjoo-52 and Indrasan rice varieties showed significantly higher growth and yield under the microbial treatments in two consecutive years. Statistical analysis showed significant (p